An online international comparison of palliative care identification in primary care using the Surprise Question. (January 2022) - White, Nicola; Oostendorp, Linda JM; Vickerstaff, Victoria; Gerlach, Christina; Engels, Yvonne; Maessen, Maud; Tomlinson, Christopher; Wens, Johan; Leysen, Bert; Biasco, Guido; Zambrano, Sofia; Eychmüller, Steffen; et al.
Background: The Surprise Question ('Would I be surprised if this patient died within 12 months?') identifies patients in the last year of life. It is unclear if 'surprised' means the same for each clinician, and whether their responses are internally consistent. Aim: To determine the consistency with which the Surprise Question is used. Design: A cross-sectional online study of participants located in Belgium, Germany, Italy, The Netherlands, Switzerland and UK. Participants completed 20 hypothetical patient summaries ('vignettes'). Primary outcome measure: continuous estimate of probability of death within 12 months (0% [certain survival]–100% [certain death]). A threshold (probability estimate above which Surprise Question responses were consistently 'no') and an inconsistency range (range of probability estimates where respondents vacillated between responses) were calculated. Univariable and multivariable linear regression explored differences in consistency. Trial registration: NCT03697213. Setting/participants: Registered General Practitioners (GPs). Of the 307 GPs who started the study, 250 completed 15 or more vignettes. Results: Participants had a consistency threshold of 49.8% (SD 22.7) and inconsistency range of 17% (SD 22.4). Italy had a significantly higher threshold than other countries ( p  = 0.002). There was also a difference in threshold levels depending on age of clinician, for every yearly increase, participants had a higher threshold. There was no difference in inconsistency between countries ( p  = 0.53). Conclusions: There is variation between clinicians regarding the use of the Surprise Question. Over half of GPs were not internally consistent in their responses to the Surprise Question. Future research with standardised terms and real patients is warranted.